A simplified and inexpensive method for the preparation of fresh or fixed bone samples for forensic histological examination. (29th July 2019) - Maggio, Ariane; Flavel, Ambika; Franklin, Daniel
ABSTRACT: The histological analysis of bone for forensic application requires thin sections to be prepared from extracted bone of suitable quality for visualization through conventional light microscopy and (if required) the measurement of microstructural features, such as osteons. While a number of protocols for the preparation of thin sections exist, they are often time consuming and complex, or require expensive and non-portable equipment. A revised protocol is presented for obtaining high quality thin sections for light microscopy and histological analyses, tested in fresh, fixed, and dry archaeological cortical bone. It does not require extensive experience, or expensive materials or equipment, and can be further adapted for use with manual tools if necessary.